Pastoralist health care in Kenya - Huka H. Duba; Ingrid M. Mur-Veeman; Arno van Raak (International Journal of Integrated Care, 2001)
Health care for the Kenyan pastoralist people has serious shortcomings and it must be delivered under difficult circumstances. Often, the most basic requirements cannot be met, due to the limited accessibility of health care provisions to pastoralists. This adds major problems to the daily struggle for life, caused by bad climatic circumstances, illiteracy and poverty. We argue that strong, integrated and community based primary health care could provide an alternative for these inadequacies in the health system. The question then is how primary health care, which integrates a diversity of basic care provisions, such as pharmaceutical provision, child delivery assistance, mother and childcare and prevention activities, can be implemented. In our view, an appropriate mix of decentralisation forms, warranting better conditions on the one hand and relying on the current community and power structures and culture on the other hand, would be the best solution for the time being.